Early and late stimulation of ob mRNA expression in meal-fed and overfed rats. - R B Harris; T G Ramsay; S R Smith; R C Bruch (The Journal of Clinical Investigation, 1996)
ob protein is hypothesized to be a circulating feedback signal in the regulation of energy balance. Obese, overfed rats have high levels of ob mRNA expression and suppressed voluntary food intake, indicating the presence of a potent satiety factor. The objectives of this experiment were to determine whether feeding rats their normal daily intake in three meals, compared with ad libitum feeding, increased ob mRNA expression and to determine the degree of obesity required to stimulate expression of ob mRNA. Rats were fed ad libitum, were tube-fed their normal intake in three meals a day, or were tube-fed twice normal intake, ob mRNA was measured by Northern blot analysis after 0, 2, 7, 14, 21, and 32 d of tube-feeding. After only 2 d ob mRNA was threefold higher in tube-fed animals than in ad libitum controls. By day 21 there was a further increase in ob mRNA expression in overfed rats which were at 130% control weight. These results suggest that a metabolic consequence of meal-feeding increases ob mRNA expression in the absence of increased food intake or weight gain. There is a further increase in ob mRNA expression once significant obesity is established.